AB0745 Subclinical atherosclerosis evolution in psoriatic arthritis patients treated with anti-tnf alpha: 5 years follow up. (15th June 2017) - Ortolan, A; Puato, M; Boschetti, G; Lorenzin, M; Hoxha, A; Punzi, L; Ramonda, R
Abstract : Background: Psoriatic arthritis (PsA) is associated with increased morbility and mortality and an accelerated atherosclerosis. Influence of anti-TNFalpha treatment (a widely used therapy in PsA) in subclinical atherosclerosis is still unclear. Objectives: The aim of this study was to evaluate subclinical atherosclerosis progression before, during and after 5 years of anti-TNFalpha treatment. Methods: Twenty-seven consecutive PsA patients were evaluated before TNF blockers therapy (T0), after 2 years (T1) and after 5 years (T2) of treatment. Subclinical atherosclerosis was evaluated through carotid duplex scanning, analyzing intima-media thickness (IMT) and flow-mediated dilation (FMD). IMT values were expressed as IMT mean (cumulative mean of all the IMT mean in every analyzed carotid segment) and M-MAX (cumulative mean of all the higher IMT in every analyzed carotid segment). Response to therapy was studied by the evaluation of tender and swollen joints (Tj and Sj), DAS 28 (disease activity score), erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). Metrologic and metabolic data were collected. For the statistical evaluation of parameters over time (T0 vs T1, T1 vs T2) Student's T test for paired data was used. Results: From T0 to T1 a deterioration in IMT-mean and M-MAX (p<0.01) was noted. At T2 IMT-mean remained stable, M-MAX worsened further (p<0.05). No significant variation in FMD was observed (Table). Noteworthy, from T0 to T2 systolic blood pressure and Body Mass Index remained stable (p=ns), while diastolic blood pressure decreased (p=0, 001). A good response to PsA treatment was confirmed by a significant decrease (T0 vs T1) in Tj, Sj, DAS 28 and CRP (p<0.01); treatment efficacy was preserved from T1 to T2 (p=ns) (Table). Conclusions: Our data revealed that in patients with PsA, despite treatment with TNF blockers, there is still a gradual, albeit slight progression of subclinical atherosclerosis assessed by ultrasonography. Other inflammatory mechanisms not related to TNF may be responsible of the progression in atherosclerotic disease. Disclosure of Interest: None declared